(untitled) (Asian Journal of Social Science Studies, 2019)
Genders play an important role to influence an individual’s buying behavior activities all the time and it acts almost the same in any other region or cultures. This study has been conducted to identify whether there is any differences exist or not according to males’ or females’ decision making style. The questionnaire has been set by using Consumer Style Inventory (CSI) approaches (α =0.895) to collect data from 133 respondents of Chattogram city, Bangladesh. The CSI has been used to identify consumer decision making style with its eight factors and 37 items. By analyzing the data it has been found that there is no significant difference in between male and female regarding their decision making style. As this study is limited to Chattogram city only, so the study has a broader scope to do further research by accommodating with more cities or countries that are culturally diversified.